2014
DOI: 10.1097/crd.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aging, Arterial Stiffness, and Cardiovascular Disease

Abstract: Coronary heart disease (CHD) is the leading cause of morbidity and mortality in the western world. Primary and secondary prevention strategies have improved tremendously. Conventional risk factors are identified and treated with intensive pharmacotherapy. Despite these measures, the incidence of CHD is on the rise in developed countries. Arterial stiffness has been identified as an independent risk factor for the development of CHD, both in the general population and in those with established CHD. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 90 publications
2
28
0
Order By: Relevance
“…4 Arterial stiffness has been identified as an independent risk factor for the development of CAD, both in the general population and in people with established CAD. 22 It has already been recognized that arterial stiffness, the main mechanism underlying pulse pressure widening, is an independent risk factor for cardiovascular disease. 23…”
Section: Discussionmentioning
confidence: 99%
“…4 Arterial stiffness has been identified as an independent risk factor for the development of CAD, both in the general population and in people with established CAD. 22 It has already been recognized that arterial stiffness, the main mechanism underlying pulse pressure widening, is an independent risk factor for cardiovascular disease. 23…”
Section: Discussionmentioning
confidence: 99%
“…68 In older patients, arterial stiffness assessed by increased PWV is associated with poor cardiovascular outcomes. 70 In the ICON1 study, carotid-femoral PWV is assessed by the Vicorder device (Skidmore Medical Limited, Bristol, UK). In addition, brachiofemoral PWV, pulse-wave analysis (includes pulse pressure, augmentation pressure and augmentation index) and ankle brachial pressure index are also assessed.…”
Section: Non-invasive Assessment Of Cardiovascular Status Arterial Stmentioning
confidence: 99%
“…Advanced aging, an irreversible biological process, is a major independent risk factor for cardiovascular in particular heart diseases 1 2 3 . Aging has been shown to promote unfavorable cardiac structural and functional alterations, including increased left ventricular wall thickness and chamber size, alterations in diastolic filling pattern such as prolonged diastole, interstitial fibrosis and decreased myocardial contractile capacity, all of which contribute to the ever-rising cardiac morbidity and mortality in the elderly 1 2 3 4 . Ample of clinical and experimental studies have suggested dramatically declined cardiac performance with aging 1 5 6 7 .…”
mentioning
confidence: 99%